Aortic Baroreceptors Display Higher Mechanosensitivity than Carotid Baroreceptors - Lau, Eva On-Chai; Lo, Chun-Yin; Yao, Yifei; Mak, Arthur Fuk-Tat; Jiang, Liwen; Huang, Yu; Yao, Xiaoqiang (Frontiers in Physiology, 2016)
Arterial baroreceptors are mechanical sensors that detect blood pressure changes. It has long been suggested that the two arterial baroreceptors, aortic and carotid baroreceptors, have different pressure sensitivities. However, there is no consensus as to which of the arterial baroreceptors are more sensitive to changes in blood pressure. In the present study, we employed independent methods to compare the pressure sensitivity of the two arterial baroreceptors. Firstly, pressure-activated action potential firing was measured by whole-cell current clamp with a high-speed pressure clamp system in primary cultured baroreceptor neurons. The results show that aortic depressor neurons possessed a higher percentage of mechano-sensitive neurons. Furthermore, aortic baroreceptor neurons show a lower pressure threshold than that of carotid baroreceptor neurons. Secondly, uniaxial stretching of baroreceptor neurons, that mimics the forces exerted on blood vessels, elicited a larger increase in intracellular Ca2+ rise in aortic baroreceptor neurons than in carotid baroreceptor neurons. Thirdly, the pressure-induced action potential firing in the aortic depressor nerve recorded in vivo was also higher. The present study therefore provides for a basic physiological understanding on the pressure sensitivity of the two baroreceptor neurons and suggests that aortic baroreceptors have a higher pressure sensitivity than carotid baroreceptors.